A new design of active NPC converter topology with higher voltage gain for solar PV applications. (December 2022) - Daula Siddique, Marif; Prathap Reddy, B.; Iqbal, Atif; Sarwar, Adil; Ahmed Memon, Mudasir; Dahri, Kamran; Mekhilef, Saad
Abstract: In the low voltage applications, the high gain multilevel inverters has seen more visibility due to the improved harmonic profile with multilevel voltage as well as boosting feature. A boost active neutral point clamped (ANPC) multilevel inverter (MLI) configuration with reduced resource count has been proposed in this paper. The proposed MLI produces 11 levels (11L) voltage with the help of 12 switches of blocking voltage ratings lesser than the peak value of output voltages. For attaining the boosting of 2.5 in output voltage, 4 capacitors are used in the proposed MLI which are inherently self-balanced. The capacitors charging as well as discharging are done by implementing the simple logic of parallel/series connection with the active power DC source. The proposed MLI is implemented and tested in the laboratory at various operating conditions, and the corresponding results and discussion are presented.